2011
DOI: 10.1111/j.1471-4159.2011.07590.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural contributions of antipsychotic drugs to their therapeutic profiles and metabolic side effects

Abstract: Antipsychotic drugs have various neuropharmacological properties as a result of their structural diversity. Despite their therapeutic benefits, most of the prescribed atypical antipsychotics can induce severe side effects, including weight gain, type II diabetes mellitus, and cardiovascular diseases. Among the developed atypical antipsychotic agents, tetracyclic dibenzodiazepine and thienobenzodiazepine compounds, particularly clozapine and olanzapine, are associated with the greatest weight gain and metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 89 publications
1
37
1
Order By: Relevance
“…approximately 30–50 % at 100 μM) [6,8]. Since hyperlipidemia and metabolic syndrome are known side effects of this family of drugs [19], we compared a set of related compounds for ability to inhibit FA transport by comparison with Grassofermata (Table 1). At best, the compounds had a modest effect in preventing PA-mediated lipid accumulation and nuclear fragmentation when provided at relatively high doses (50 and 100 μM).…”
Section: Resultsmentioning
confidence: 99%
“…approximately 30–50 % at 100 μM) [6,8]. Since hyperlipidemia and metabolic syndrome are known side effects of this family of drugs [19], we compared a set of related compounds for ability to inhibit FA transport by comparison with Grassofermata (Table 1). At best, the compounds had a modest effect in preventing PA-mediated lipid accumulation and nuclear fragmentation when provided at relatively high doses (50 and 100 μM).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that weight gain or obesity might not be a single crucial factor for onset of metabolic side-effects, such as insulin resistance anddyslipidemia 42 . Notably, previous studies reported that OLZ and CLZ had a similar antagonist activity at histaminergic subtype 1 (H 1 ) receptors, and the affinity for H 1 receptors played a key role in drug-induced weight gain 53, 54 , however, metabolic side-effects could be associated with their plasma concentrations 55 . Further studies investigating a possible association between SGA serum concentrations and metabolic outcomes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they also target the serotonin receptor subtype 2A (5HT 2A ) [19] which may help to reduce the negative side-effects associated with typical antipsychotics [19, 20]. It is important to note that the proper correlation between the ratio of the clinical dosage and D 2 receptor affinity necessary to treat the symptoms of conditions such as schizophrenia has not been completely established [21]. …”
Section: Introductionmentioning
confidence: 99%